Effect of core-shell microspheres as pore-forming agent on the properties of porous alumina ceramics. (5th January 2017) - Han, Meikang; Yin, Xiaowei; Cheng, Laifei; Ren, Sa; Li, Zhengkun
Abstract: The porous alumina ceramics with closed pores were fabricated using C@Al2 O3 microspheres as pore-forming agent. The closed pores with a diameter about 5 μm were successfully obtained in the dense matrix, owing to the additive C@Al2 O3 microspheres. Different amount of C@Al2 O3 microspheres was added to investigate the effects of closed pores on thermal, dielectric and mechanical properties. With the increasing microspheres amount, the closed porosity of alumina ceramics ranges from 5.82 to 14.5%, the thermal conductivity decreases continuously at the temperature ranging from 30 to 1200 °C, and the flexural strength and fracture roughness decrease. As the closed porosity increases, the real permittivity decreases, while the tangent loss has a slight increase. When the mass ratio of C@Al2 O3 microspheres is 10 wt.%, the porous alumina ceramics with the thermal conductivity (13.07–3.8 W·m − 1 ·K − 1 ), the flexural strength (97.05 ± 18 MPa), and the fracture roughness (2.65 ± 0.13 MPa·m 1/2 ) can be obtained. Graphical abstract: Highlights: The closed pores in alumina ceramics were achieved using core-shell structured C@Al2 O3 microspheres as pore-forming agent. The closed pores significantly decreased the thermal conductivity to 3.8 W·m − 1 ·K − 1 at 1200 °C. The closed pores decreased the real permittivity from 9.74 to 7.48 with a slight increase of the imaginary permittivity.